Freshwater Fish Cultivation Innovation and Its Development Potential in Fitu Village Ternate City, North Maluku Province - Andriani, Rovina; Muchdar, Fatma; Malan, Sudirto; Sardi Titaheluw, Syahnul (Universitas Muhammadiyah Palembang, 2021)
Budikdamber is cultivating fish and vegetables in one bucket, which is an aquaponic system. Usually, the aquaponics system developed so far requires pumps and filters, requiring electricity, ample land, expensive and complicated costs. The concept is simple and does not require significant capital, and it does not need a large room or pool to be an added value of this technology. The Budikdamber technique can be one of the community's solutions to innovate fish and vegetable cultivation at once in one container. In addition, with the current state of the COVID-19 pandemic, Budikdamber activities can be a solution for family food security. Community service was carried out in Fitu Village, South Ternate District, in June 2021. The objectives of this community service are Providing information to the public on how to use the narrow land on the terraces and yards for fish and vegetable cultivation in buckets so that people can maintain food security during the current COVID-19 pandemic. Budikdamber (Fish Cultivation in Buckets) cultivates fish and vegetables in one bucket: an aquaponics system (fish and vegetable polyculture) as a community solution in providing food needs COVID-19 pandemic. It could use as a business opportunity to help the family economy.